Pyrolysis of different biomass: Direct comparison among Posidonia Oceanica, Lacustrine Alga and White-Pine. (15th January 2016) - Chiodo, V.; Zafarana, G.; Maisano, S.; Freni, S.; Urbani, F.
Highlights: Different kinds of biomass were selected to carry out pyrolysis experiments. The experiments were conducted in a fixed bed reactor at different temperatures. Bio-oil and bio-char characterization was carried out. The yield of bio-oil from pyrolysis process was evaluated. Abstract: An investigation on the feasibility of producing bio-oil and bio-char fuels from wood chips (White-Pine), a Mediterranean seaweed (Posidonia Oceanica) and a local freshwater alga (Lacustrine Alga) by pyrolysis was carried out. Experiments were performed in a fixed bed reactor at different temperatures (400, 500 and 600 °C). Thermo-gravimetric analysis (TGA/DTG) were used in order to investigate the pyrolytic behavior. Product yields and composition from algal pyrolysis were compared with those obtained from terrestrial biomass. Yields of char were in the range 22–48 wt% for algae and 20–27 wt% for lignocellulosic biomass. Due to the higher ash content (17–38%), the char obtained from algal biomasses had a lower heating value than that from White-Pine chips. By contrast, the oil yields from algae varied between 34 and 55 wt%, whereas yields from lignocellulosic biomass were in the range of 41.4–47.2%. The oil from Posidonia Oceanica showed a high heating value (HHV = 26.1 MJ/kg) close to the value of the oil obtained from White-Pine (30.1 MJ/kg). Chemical composition of liquid samples obtained at 500 °C was analyzed by GC–MS to identify organic functional groups.